Investigating Socially Mediated Educational Communication through WhatsApp and Telegram: Perception and Preference of Students and Teachers - Sunita Saikia; Mohammad Asif; Yeasmin Sultana (Indian Journal of Educational Technology, 2024)
The COVID-19 pandemic has compelled the academic community to choose various social networking applications as an important avenue for interaction with students and teachers. WhatsApp and Telegram applications have emerged as efficient tools in the education process. With this background, the present study aimed to explore the perception and preferences of students and teachers towards the use of WhatsApp and Telegram as educational tools. The study used the descriptive quantitative method to collect data from 150 samples (100 UG students and 50 UG teachers) through a convenience sampling technique. A self-developed perception questionnaire with a Cronbach Alpha value of 0.917 was used to gather data. The percentage analysis indicated that the majority of the teachers have a favourable perception of the use of WhatsApp and Telegram as educational tools. However, the majority of the students have a favourable perception of the use of WhatsApp and a neutral perception of the Telegram application. The result found that both students and teachers mostly prefer WhatsApp as an effective tool in the education process.